The effect of incentives on employee performance at Bank NTT Head Office in Kupang - Struce Andriyani; Cahya Surya Abubakar (Journal of Management Small and Medium Enterprises (SMEs), 2026)
Employee performance is a critical determinant of organizational effectiveness, particularly in the banking sector, where human capital plays a central role in achieving strategic objectives. Incentive systems are widely recognized as an important mechanism for motivating employees and enhancing workplace productivity. This study examines the effect of incentives on employee performance at Bank NTT Head Office in Kupang, Indonesia. Employing a quantitative research design, the study involved a population of 332 employees, from which 77 respondents were selected as the research sample. Data were analyzed using descriptive statistical techniques and simple linear regression analysis to evaluate the relationship between incentives and employee performance. The descriptive findings indicate that both the incentive system and employee performance are perceived to be at very good levels within the organization. The inferential analysis demonstrates that incentives have a positive and statistically significant effect on employee performance, as evidenced by the t-test results. Furthermore, the coefficient of determination indicates that incentives make a substantial contribution to explaining variations in employee performance. These findings suggest that well-designed incentive programs can serve as an effective human resource management strategy for improving employee productivity and organizational outcomes. The study contributes to the literature on employee motivation and performance by providing empirical evidence from the Indonesian banking industry and offers practical implications for organizations seeking to enhance workforce performance through performance-based reward systems. Keywords: Incentives; Employee Performance; Bank NTT